A review of isolation and identification of bioactive components from Murdannia species / Audrey Osong Patrick and Nor Aziyah Bakhari - Patrick, Audrey Osong; Bakhari, Nor Aziyah (2020)
The term of medicinal plants includes a variety of plants used in herbalism and some of these plants possessed activities suitable for the medicinal area which can be processed for drug development and synthesis. These plants recommended for their potency in treating diseases and illnesses. This study consists of the review on the bioactive components that had been identified in the Murdannia species as well as the methods used to isolate and identify the these bioactive compounds by using collection of relevant information, articles, journals and books by searching in various databases. UV-Vis spectrophotometer used on M. bracteata identified 10% of gallic acid equivalent of phenolic compounds. GC-MS analysis were able to identify α-tocopherol, β- sitosterol and stigmasterol in M. bracteata. Then shows presence of 2-Furanone,3,4- dihydroytetrahydro, 4H - Pyran -4-one,2,3 - dihydro -3,5- dihydroxy-6-methyl, 1,2,3- Propanetriol, diacetate in M. Lanugnosa and shows the presence of salicylaldehyde, azine and diphenylfurazan N-oxide furazan, diphenyl-, 2-oxide 3,4-diphenylfurazan 2-oxide diphenylfuroxan in M. simplex. Caffeic acid and apigenin are found in hexane extract of M. bracteata determined by using UPLC analysis. NMR spectroscopy used on ethanolic extract of M. loriformis shows presence of 3b-O- D-glucopyranosyl-24n-ethylcholest-5-ene and β-O-Dglucopyranosyl- 2-(2-hydroxy-Z-6-enecosamide)-sphingosine. Standard colour test determines the presence of alkaloids and steroids in ethanolic extract of M. loriformis, then, tannins, saponins, alkaloids and flavonoids in methanolic extract of M. nudiflora, and, phytosterols, alkaloids and flavonoids in ethanolic extract of M. nudiflora. It is suggested that other isolation and identification methods are used on these plants to determine presence of other bioactive compounds.